Active vibration control in specific zones of smart structures. (March 2019) - Wang, Peng; Korniienko, Anton; Bombois, Xavier; Collet, Manuel; Scorletti, Gérard; Skow, Ellen; Wang, Chuhan; Colin, Kévin
Abstract: Smart structures are light structures with integrated sensing and actuating capabilities (smart materials). In this paper, the use of such smart materials for active vibration control is considered, in the case where the vibration covers a large frequency band and the vibration has to be reduced in a region where neither actuation nor sensing is possible. An accurate model combining physical and data-based modeling is developed. A multi-variable H ∞ controller achieving the desired control objective and taking into account the robustness issues is computed. The validity of the proposed approach is verified on an experimental setup.